Pengembangan Kurikulum Pendidikan Islam - Nasir, Muhammad (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
The Qur'an asserts that the purpose of human creation is to serve (al-Ibadah) to Allah. Serving in this case includes the meaning of submission, helplessness, weakness, servitude, obedience and obedience of man to the law of God in living life on earth, whether ritual worship concerning vertical relationship (habl min Allah) and social worship concerning horizontal (hablun min al -Nas). The purpose of human creation is basically the ultimate goal of Islamic education. In order to achieve the goal of human creation as well as the goals of Islamic education above, the setting of objectives, content and teaching materials, learning strategies and evaluation of Islamic education becomes very important to do. Setting objectives may include the arrangement of the herarchical side of the broadest goal to the most narrow goals and objective categories of spiritual, social, knowledge and skill objectives. While the content setting can cover the breadth and depth of material including the development of teaching materials that support. Strategy settings include various models, approaches, strategies, methods, techniques and learning experiences that facilitate the delivery of content and teaching materials to achieve goals. Furthermore, the assessment arrangement includes various types of penilian either in the form of assessment that besifat qualitative or quantitative or assessment that is test or non test.